Cannabis and Driving: Developing Guidelines for Safety Policies - Manetti, Federico; Chericoni, Silvio; Marrocco, Anna; Scopetti, Matteo; Padovano, Martina; Santurro, Alessandro; Frati, Paola; Gabbrielli, Mario; Fineschi, Vittorio (Current Pharmaceutical Biotechnology, 2023)
Introduction: The dynamism in the regulatory frameworks concerning the consumption of cannabinoids has placed their effects on cognitive and psychomotor skills at the center of the scientific debate. In consideration of the potential repercussions on public safety, particular attention has been focused on the impairment of driving skills, opening up the need to specifically regulate driving under the effects of cannabinoids. Pharmacokinetics: Both native cannabinoids and metabolites show a long positivity at low concentrations in the biological fluids, especially in the case of chronic consumption. Qualitative positivity to cannabinoids does not itself prove the presence of detrimental effects, which require the presence of active substances at relevant concentrations. Driving Skill Impairment: Multiple studies highlight a tetrahydrocannabinol (THC) concentration- based alteration of driving skills mainly affecting automatisms, whereas skills subjected to cognitive control are preserved up to higher dosages. The evidence relating to associations with other substances, chronic consumption and other cannabinoids, on the other hand, is still burdened by a high degree of uncertainty. Regulation Policies: Different models can be adopted in the regulation of driving under the effects of cannabinoids: sanctions can be applied in case of qualitative positivity, cannabinoids concentration above a defined threshold, or in presence of a demonstrated state of cognitive alteration. Conclusion:
Keywords: zero tolerance